Markers and function of human NK cells in normal and pathological conditions. Issue 2 (12th February 2017) - Del Zotto, Genny; Marcenaro, Emanuela; Vacca, Paola; Sivori, Simona; Pende, Daniela; Della Chiesa, Mariella; Moretta, Francesca; Ingegnere, Tiziano; Mingari, Maria Cristina; Moretta, Alessandro; Moretta, Lorenzo
Abstract : Natural killer (NK) cells, the most important effectors of the innate lymphoid cells (ILCs), play a fundamental role in tumor immune‐surveillance, defense against viruses and, in general, in innate immune responses. NK cell activation is mediated by several activating receptors and co‐receptors able to recognize ligands on virus‐infected or tumor cells. To prevent healthy cells from auto‐aggression, NK cells are provided with strong inhibitory receptors (KIRs and NKG2A) which recognize HLA class I molecules on target cells and, sensing their level of expression, allow killing of targets underexpressing HLA‐class I. In vivo, NK cell‐mediated anti‐tumor function may be suppressed by tumor or tumor‐associated cells via inhibitory soluble factors/cytokines or the engagement of the so called immune‐check point molecules (e.g., PD1‐PDL1). The study of these immune check‐points is now offering new important opportunities for the therapy of cancer. In haemopoietic stem cell transplantation, alloreactive NK cells (i.e., those that express KIRs, which do not recognize HLA class I molecules on patient cells), derived from HSC of haploidentical donors, are able to kill leukemia blasts and patient's DC, thus preventing both tumor relapses and graft‐versus‐host disease. A clear correlation exists between size of the alloreactive NK cell population and clinical outcome. Thus, in view of the recent major advances in cancer therapy based on immuno‐mediated mechanisms, the phenotypic analysis of cells and molecules involved in these mechanisms plays an increasingly major role. © 2017 International Clinical Cytometry Society